Biobehavioral Reactivity to Social Evaluative Stress in Women With Borderline Personality Disorder - Scott, Lori N. (2012)
Several clinical theories propose that borderline personality disorder (BPD) is characterized by a biologically based affective vulnerability to intense affective experiences and impaired modulation of affective states, which might manifest in high emotional intensity, hyperreactivity, and impaired recovery to baseline. However, few studies have tested these theories based on emotional and biological responses of BPD participants in response to psychosocial stressors. This study examined cortisol, alpha-amylase, and subjective emotional reactivity to social evaluative stress among women with BPD compared with two healthy female control groups: a trait-matched (TM) group scoring similarly to the BPD group on trait measures of negative affect and impulsivity, and a non-trait-matched (NTM) group. Results generally suggested high emotional intensity and high baseline psychobiological arousal among individuals with BPD, but not emotional hyperreactivity or impaired recovery specific to the stressor. Relative to both control groups, BPD participants had higher baseline and overall subjective negative affect, higher baseline cortisol levels, and attenuated stress-related cortisol reactivity. In addition, both the BPD and TM groups had attenuated alpha-amylase reactivity in comparison to the NTM group. The differences between BPD and TM groups on most of the dependent measures suggest that emotional dysregulation in BPD is not merely an extreme variant of normative personality traits. These results suggest that women with BPD demonstrate intense and chronic negative affectivity along with high resting psychobiological arousal and attenuated psychobiological reactivity specific to laboratory stressors.